The impact of using the Power Point program on the achievement of the 10th grade students in Physical Education in Al Buraimi Governorate, Sultanate of Oman - Al Shamsi, Hamid bin Rashid bin Humaid (Journal of Educational and Psychological Sciences, 2018)
The aim of this research is to identify the impact of using presentations on the educational attainment of tenth graders in physical education. To achieve this purpose the study focused on the experimental approach, and the two groups were chosen: the experimental and the controlled with a before and an after test. The researcher has prepared a collective test alongside with physical education tests that are measured by observation card. The experiment was applied on a random group of tenth graders in one of ALBuraimi schools, also, collective test and the observation card were applied on a group of (40) students divided randomly into two equal groups, one was the controlled group; that studied in the traditional way, and the other one was the experimental group which used the presentations. The research tools were applied before on both groups in the first semester of the year 2016/2017. At the end of the experiment the research tools were applied afterwards on both groups. The results indicated the statistically significant differences at the level of (0.05), between the average of students marks of the two groups the experimental and the controlled in applying the afterwards for the collective test, where the experimental group got an average of (25.29), on the other side the controlled group that got an average of (19.18). Also, the performance test for the physical education which is measured by the observation card and the experimental group got an average of (7.37), on the other side, the controlled group got an average of (4.55), and the difference in the collective test and the observation card is clear and in favor of the experimental group. In the view of these results there were some suggestions and recommendation that been suggested.